The first Iraqi experience in sacral neuromodulation for patients with lower urinary tract dysfunction - Issam S. Al-Azzawi (Taylor & Francis Group, 2018)
Objectives: To present our experience, in Iraq, with sacral neuromodulation (SNM) in patients with refractory lower urinary tract dysfunction, with discussion of the factors that affect the response rate. Patients and methods: In this prospective, clinical, interventional study, 24 patients were evaluated and treated by a team comprised of a Urologist and a Neurosurgeon with SNM over a 1.5-year period. The gender, age, pathology, and clinical presentation, were all studied and evaluated. Successful clinical response was defined as achieving a ≥50% improvement in voiding diary variables. Results: The mean age of those that responded to SNM was 28 years, with females responding better than males (10 of 14 vs four of 10). The SNM response rate according to presentation was six of 10 in those with overactive bladder/urge urinary incontinence, six of nine of those with urinary retention, and two of five in those with a mixed presentation. The response rate in idiopathic voiding dysfunctions was 11 of 13, whilst for neurogenic dysfunctions it was three of 11. Other benefits such as in bowel motion, erectile function, menstruation, power of lower limbs, and quality of life (QoL), were also recorded. The complications were reasonable for this minimally invasive procedure. Conclusion: SNM offers a good and durable solution for some functional bladder problems, if patients are well selected. There may also be additional extra-urinary benefits that contribute to improvements in QoL. SNM was well tolerated by our patients with an encouraging response rate, especially in psychologically stable patients with idiopathic dysfunctions. Keywords: Lower urinary tract dysfunction, Overactive bladder, Urge urinary incontinence, Urinary retention, Neuromodulation